The role of employee age in hybrid work: First findings from a systematic review - Michel, A.; Sousa, I.C.; Scheibe, S.; Goštautaitė, B.; Picco, E.; Gu, X.; Vrachimi, M. (22nd Congress of the European Association of Work and Organizational Psychology (EAWOP), 2025)
The objective. Many workers, particularly in white-collar roles, have the opportunity to work in hybrid settings. Following Lauring and Jonasson (2024) recent definition, hybrid work can be first characterized by location (e.g. switching between working on-site in the office or remotely at home), second, by modality (e.g., switching between face to face and virtual meetings) and, third, by temporality (e.g., working together synchronously vs asynchronously). However, so far, there has been no systematic review of the literature focussing on characteristics, practices and outcomes of hybrid work in relation to age, and on how older workers (vs. workers that are younger) adopt and adapt to different characteristics of hybrid work and practices. Such insights are important in light of the aging workforce across the developed world and growing prevalence of hybrid work formats. Methods. We systematically identify and review empirical studies focussing on hybrid work, age, and their association with four groups of work outcomes: health and well-being, performance and productivity, work engagement and motivation, and career-development. Results. The work on the systematic review is in progress. Preliminary results will be presented in this talk. Conclusions. We will present first findings of the systematic review and discuss them in relation to age-inclusive management and the implications for designing hybrid work for different age groups.